Envenomation by Centruroides pococki scorpion with neuromuscular toxicity. (30th January 2021) - Caré, Weniko; Larréché, Sébastien; Busser, Paul; Dufayet, Laurène; Vodovar, Dominique; de Haro, Luc; Langrand, Jérôme
Abtract: Cases of human envenomation by Centruroides pococki are exceptionally reported in human. We report a Class III human envenomation by C. pococki in Guadeloupe, French West Indies, with neuromuscular toxicity that has never been described before. Symptoms resolved within a few hours, without the need for intravenous scorpion-specific antivenom. Highlights: The epidemiology of scorpionism is still poorly known because of under-reporting. Cases of human envenomation by Centruroides pococki are exceptionally reported in human. We report a Class III human envenomation by C. pococki with neuromuscular toxicity.